Determination of Epicenters before Earthquakes Utilizing Far Seismic and GNSS Data: Insights from Ground Vibrations - Chen, Chieh-Hung; Lin, Li-Ching; Yeh, Ta-Kang; Wen, Strong; Yu, Huaizhong; Yu, Chen; Gao, Yongxin; Han, Peng; Sun, Yang-Yi; Liu, Jann-Yenq; Lin, Cheng-Horng; Tang, Chi-Chia; et al. (Remote sensing (Basel, Switzerland), 2020)
Broadband seismometers, ground-based Global Navigation Satellite Systems (GNSS), and magnetometers that were located within an epicentral distance of approximately 150 km consistently observed the novel anomalous behaviors of the common-mode ground vibrations approximately 5–10 days before the M6.6 Meinong earthquake in Taiwan. The common-mode ground vibrations with amplitudes near 0.1 m at frequencies ranging from 8 × 10−5 to 2 × 10−4 Hz were generated near the region close to the epicenter of the impending earthquake. The common-mode vibrations were consistently observed in seismic and GNSS data associated with five other earthquakes in four distinct areas. The results reveal that the common-mode vibrations could be a typical behavior before earthquakes. The causal mechanism of common-mode vibrations can be attributed to crustal resonance excitations before fault dislocations occur. Potential relationships with other pre-earthquake anomalies suggest that the common-mode vibrations could be ground motion before earthquakes, which was investigated for a significant length of time.